ABOUT THE NECESSITY OF INTERNATIONAL COOPERATION IN REGULATING POPULATION MIGRATION - Matchanov Alimjan Atabaevich (Scholar Express Journals, 2023)
The article analyzes the current state of the problems associated with population migration in the modern world community, examines the concept, types of migration and the need for further improvement of international cooperation in regulating migration processes in the world
Keywords: : international cooperation; migration; types of migration; regulation of the migration process